Low-density lipoproteins cause atherosclerotic cardiovascular disease: pathophysiological, genetic, and therapeutic insights: a consensus statement from the European Atherosclerosis Society Consensus Panel. (13th February 2020) - Borén, Jan; Chapman, M John; Krauss, Ronald M; Packard, Chris J; Bentzon, Jacob F; Binder, Christoph J; Daemen, Mat J; Demer, Linda L; Hegele, Robert A; Nicholls, Stephen J; Nordestgaard, Børge G; Watts, Gerald F; et al.
Abstract: